Overexpression of c-Myc triggers p62 aggregation-mediated mitochondrial mitophagy in cabozantinib resistance of hepatocellular carcinoma - Kaibo Yang; Xing Zhang; Kun Yang; Sinan Liu; Jingyao Zhang; Yunong Fu; Tong Liu; Kunjin Wu; Jing Li; Chang Liu; Qichao Huang; Kai Qu (Molecular Medicine)
Abstract Resistance to tyrosine kinase inhibitors (TKIs) poses a significant challenge in the treatment of hepatocellular carcinoma (HCC). Although dysregulation of mitochondrial dynamics has been implicated in the aggressive behaviors of various tumors, the specific role and underlying mechanisms by which this dysregulation contributes to cabozantinib resistance in HCC cells remains insufficiently characterized. By investigating mitochondrial dynamics as central regulators of cabozantinib resistance, this work specifically aims to discover actionable targets for restoring drug sensitivity in treatment-refractory HCC cells. We employed transmission electron microscopy (TEM) and confocal microscopy to analyze mitochondrial morphology in HCC cells resistant to TKIs. Additionally, we utilized an oncogene hydrodynamic injection-induced primary liver cancer mouse model to assess the therapeutic efficacy of combining cabozantinib with other pharmacological agents. Our results demonstrated significant increases in mitochondrial fragmentation, p62 aggregation, and mitophagy in cabozantinib-resistant HCC cells, which correlated with overexpression of c-Myc. Notably, inhibiting mitochondrial fission, p62 aggregation, or autophagy effectively reversed the resistance of HCC cells to cabozantinib. Mechanistically, cabozantinib treatment was shown to induce c-Myc expression, which significantly enhanced mitochondrial fragmentation and p62 aggregation, thereby promoting mitophagy. This mitophagic process selectively eliminated damaged mitochondria, reducing cytochrome C-induced apoptosis in cabozantinib-resistant cells. Ultimately, combining cabozantinib with either the autophagy inhibitor chloroquine or the p62 aggregation inhibitor XRK3F2 resulted in improved anticancer efficacy. In conclusion, c-Myc overexpression facilitates p62 aggregation-mediated mitophagy, leading to cabozantinib resistance in HCC cells. Inhibition of autophagy effectively restores cabozantinib sensitivity in HCC.